Canadians’ Views on Canada’s Energy Future University of Ottawa Positive Energy Summary, National Survey conducted by Nanos Research for the University of Ottawa - Nanos Research; Positive Energy (Université d'Ottawa | University of Ottawa, 2015)
Overall Canadians generally believe that it is possible to develop resources while protecting the environment and are supportive of investments in the renewable energy sector. They also clearly expect the federal government to take the lead and think the national interest is more important than local, provincial or Aboriginal views.
Keywords: Energy Policy; Surveys; Public Opinion; Climate Change